The Role of Protected Areas in Conserving Tropical Forests: A Review - Hussain, Sara; Iqbal, Kiran; Shah, Ahmed (Yayasan Adra Karima Hubbi, 2024)
Protected areas are critical for the conservation of tropical forests, which are among the most biodiverse ecosystems on the planet. These areas play a vital role in safeguarding wildlife, preserving ecological processes, and mitigating the impacts of climate change. However, the effectiveness of protected areas in achieving these conservation goals varies significantly. This review aims to assess the role of protected areas in conserving tropical forests by analyzing their effectiveness, management practices, and socio-economic impacts. The study seeks to identify best practices and challenges faced in the management of these areas. A comprehensive literature review was conducted, synthesizing findings from peer-reviewed articles, government reports, and case studies related to protected areas in tropical forest regions worldwide. Key metrics such as biodiversity outcomes, habitat preservation, and community engagement were evaluated. The findings indicate that well-managed protected areas significantly contribute to biodiversity conservation and forest preservation. However, challenges such as illegal logging, encroachment, and insufficient funding hinder their effectiveness. Successful case studies highlight the importance of community involvement and adaptive management strategies in enhancing conservation outcomes. The study concludes that protected areas are essential for conserving tropical forests, but their effectiveness is contingent upon effective management and stakeholder engagement. Strengthening governance frameworks and increasing funding for these areas are crucial for ensuring their long-term success in biodiversity conservation.